2016
DOI: 10.1002/ajpa.23031
|View full text |Cite
|
Sign up to set email alerts
|

Constructing cranial ontogenetic trajectories: A comparison of growth, development, and chronological age proxies using a known‐age sample of Macaca mulatta

Abstract: Recent morphometric research has generated opposing conclusions regarding the ontogenetic trajectories of catarrhine crania, possibly due to the ontogenetic proxies used to calculate them. Therefore, we used three surrogates: size, molar eruption, and chronological age to generate trajectories in a known-age sample to produce ontogenetic trajectories and determine the similarities and differences between them. Forty-three landmarks from an ontogenetic series of 160 Macaca mulatta crania, with associated ages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Due to the scarcity of subadult specimens available in museum collections for some species, and the need to obtain reasonable sample sizes, mixed‐sex samples were used to construct each species’ ontogenetic trajectory. The use of mixed‐sex samples to construct ontogenetic trajectories is justified by previous investigations which found that male and female ontogenetic trajectories do not typically diverge until late in ontogeny, and that mean juvenile cranial shapes are often indistinguishable between sexes (Collard & O’Higgins, 2001; Leigh, 2006; O’Higgins & Collard, 2002; O’Higgins & Jones, 1998; Simons & Frost, 2016; Singleton et al, 2010). However, it should also be noted that even closely related species can vary widely in levels of sexual dimorphism (see Schaefer et al, 2004), and, as this is a mixed‐sex sample, information about the scale of interspecific levels of sexual dimorphism is not accounted for in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the scarcity of subadult specimens available in museum collections for some species, and the need to obtain reasonable sample sizes, mixed‐sex samples were used to construct each species’ ontogenetic trajectory. The use of mixed‐sex samples to construct ontogenetic trajectories is justified by previous investigations which found that male and female ontogenetic trajectories do not typically diverge until late in ontogeny, and that mean juvenile cranial shapes are often indistinguishable between sexes (Collard & O’Higgins, 2001; Leigh, 2006; O’Higgins & Collard, 2002; O’Higgins & Jones, 1998; Simons & Frost, 2016; Singleton et al, 2010). However, it should also be noted that even closely related species can vary widely in levels of sexual dimorphism (see Schaefer et al, 2004), and, as this is a mixed‐sex sample, information about the scale of interspecific levels of sexual dimorphism is not accounted for in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses in the present investigation were performed on two aspects of cranial postnatal ontogeny: (a) trajectories of shape change associated with size (allometric trajectories), and (b) trajectories of shape change associated with molar eruption stage (ontogenetic trajectories). Although these trajectories track similar aspects of shape change associated with ontogeny (Simons & Frost, 2016; Holly Smith et al, 1994), we use both of them to address separate aspects of ontogenetic trajectories. That is, we use cranial size to compare patterns of allometry among taxa, and we use the amount of shape changes that occur over similar stages of development (ontogenetic trajectories), from the full eruption of the deciduous dentition to full adult dentition, to examine if taxa differ in the magnitude of ontogenetic shape changes.…”
Section: Introductionmentioning
confidence: 99%
“…Dental age groups were used for basicranial development proxy instead of size. This facilitated the comparison of individuals at different ontogenetic stages irrespective of absolute size, which is known to differ between humans and chimpanzees in both the adult values and growth curves (Scott et al, ; Simons & Frost, ). A detailed description of the chimpanzee and modern human sample with information regarding every individual used here is provided in the excel sheet file as Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…In order to analyze ontogeny, we use the same phenotypic trajectories approach. In our case, as different phenotypic levels, we use dental eruption stages, a reliable proxy for ontogenetic comparison (Simons & Frost, ). This approach allows us to investigate nonlinear trajectories that most often are difficult to quantify with conventional methods (Adams & Collyer, ; Collyer & Adams, , ; Gunz, Neubauer, Maureille, & Hublin, ; Mitteroecker et al, ; Mitteroecker, Gunz, & Bookstein, ; Scott et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Hungarian juveniles and Georgian adults have strong variation in lnCS, but not so the Hungarian adults. Dental age provides a stronger variable than lnCS for simulating ontogenetic trajectory (Simons & Frost, ) and returned a stronger R 2 correlation of 0.467 for the Hungarian juvenile and adult crania, than the Hungarian juvenile and Georgian adult crania, which returned an R 2 of 0.363 (Table ). A correlation of PD and dental age with lnCS as a covariate increased the correlation to R 2 of 0.684 for the Hungarian juvenile and adult crania and R 2 of 0.61 for the Hungarian juvenile and Georgian adult crania.…”
Section: Resultsmentioning
confidence: 99%